Towards integrated reporting: The inclusion of content elements of an integrated annual report in the chairmen's statements of JSE-listed companies - N. Mmako; M. Jansen van Rensburg (South African Journal of Business Management, 2017)
A call for greater transparency following various corporate scandals in a volatile global economy has placed intense pressure on South African corporations to reform, not only their conduct but also their reporting. As investors and other stakeholders insisted on the assurance that company practices were transparent, accountable and fair to all stakeholders, the JSE changed listing requirements to oblige listed companies to integrate their sustainability reports with their annual reports. To understand how companies incorporate integrated reporting standards in voluntary narrative disclosures, this article reports on how chairpersons of 50 high-performing and 50 poor-performing companies listed on the JSE included content elements within their statements. Qualitative content analysis was used to analyse how content elements were presented and communicated in the 2012 chairpersons' statements. Findings indicate that South African companies embraced new reporting requirements. Just as the King Reports have been praised as an internationally leading code of governances, annual corporate reports of JSE-listed companies can become an international benchmark for integrated reporting. Even though the chairperson's statement does not present the platform to discuss all the content elements in detail, the content elements of integrated reporting seem to provide a useful framework for chairpersons on what to include in their chairperson's statement.
Keywords: 650